Multiculturalism as a reflection in the decorative motif in Malaysia traditional buildings - Zainal Abidin, Norzalifa; Jahn Kassim, Puteri Shireen; Raja Abdul Kadir, Tengku Anis Qarihah (University College of Technology Sarawak (UCTS), 2019)
Multiculturalism is under constant debate as to how it is linked to developing inclusive identity in the facades of public buildings: yet it must be rooted in overall local identity. The richness of this multiculturalism elements is reflected in the various motifs applied in the traditional public buildings. Influences of this Multiculturalism will also be discussed in this paper. The paper reviews a series of composition analyses of the motifs in the building components and elements of palaces, an aristocratic house and a mosque in Malaysia in order to study the composite elemental vocabulary based elements and the links to the local endemic Malay identity and traditional decoration motifs from the selected building elements; such as wall and ventilation panels, door leafs, staircases and balustrades are extracted n studied morphologically. Case study taken from Balai Besar Kedah, (1896) Istana Jahar (1887) Kota Bharu, Istana Bandar (1903) Kelang, Rumah Panglima Ghani Melaka and Masjid Tengkera Melaka (Malaysia). The motifs are broken down into constituent multicultural components and elements to show vocabulary and usage of colour which also reflect the symbolic meanings behind these motif compositions. The basic understanding of these elements are shown to reflect the multiculturalism richness and vocabulary used in these decoration motifs.